Trajetória do mercosul e mudança de paradigmas e de posiç\~oes da política externa Brasileira: Começo virtuoso e crise recente. Possíveis interpretaç\~oes - Sérgio Florêncio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper assumes that Mercosur has been under a crisis for the last four years, the main symptoms of which are: decreasing priority in the context of Brazilian Foreign Policy (BFP); growing number of exceptions within its Common External Tariff (CET); decreasing number of Mercosur decisions embodied in each country's domestic legal framework; Mercosur's incapacity to effectively negotiate free trade agreements (FTAs). Changes in BFP's paradigms and positions are used as main parameters for the crisis' examination. Five interpretations for Mercosur's crisis are studied, within the scope of both that theoretical (paradigms) and empirical (positions) framework: i) adoption of an intergovernmental model, instead of a supranational one; ii) paradigm change in BFP's, from an Americanist/pragmatic institutionalist (under President Cardoso) to an autonomist (under Presidents Lula and Dilma); iii) Unasur's creation, as a source of Mercosur's weakening and IIRSA's politicization; iv) Mercosur's incapacity to embody a hub and spoke pattern of integration; and v) Brazil's and Argentina's foreign policy polarization under Menen and Cardoso as well as both countries' interventionist economic policies under the Kirchners and Lula/Dilma. The paper's conclusions identify interpretations i), ii), iii) and iv) as adequate explanations for the crisis. Effective measures to overcome Mercosur's crisis are also presented.
Keywords: F15; 330; Mercosur; Brazilian foreign policy; regional integration